Environmental chemistry and ecotoxicology of heavy metals in water, sediment, and aquatic plants in lotic ecosystem - Nabaa Shakir Hadi (Environmental Health Engineering and Management, 2024)
Background: This study examined the effects of the Al-Rustumiya sewage treatment station on the heavy metals (Fe, Zn, and Mn) that pollute the Diyala River. Methods: Samples of water, sediment, and aquatic vegetation were collected monthly from Diyala River at four locations between March 2022 and February 2023. The samples were collected using standard sampling methods and analyzed with an atomic absorption spectrophotometer. Results: The order of heavy metals in water was: Fe > Mn > Zn, both in the dissolved and particulate phases. The sediment was ordered in the exchangeable and residual phases: Fe > Mn > Zn, while in aquatic plants, the order in leaves was: Fe > Zn > Mn, and in roots: Zn > Fe > Mn. According to the findings, the particulate phase of water contained greater quantities of heavy metals than the dissolved phase. The sediment concentrations in the residual phase exceeded those in the exchangeable phase, while the roots of aquatic plants had higher concentrations than their leaves. Conclusion: As Al-Rustumiya station’s streams flow into the river, the concentrations of heavy metals in the water increase. This has a deleterious effect on aquatic life and the agricultural area on both sides that rely on the river’s water for irrigation. This research concentrates on the destiny and processes of transmission in the lotic aquatic system for heavy metals (Fe, Zn, and Mn). As there is a cumulative effect from these metals, appropriate measures are necessary by the relevant agencies to address this problem.